Trainee Teachers: Perceptions and Attitudes Toward STEAM Education, systematic literature review - Heredia-Sacio, María del Rosario (2025)
Introduction. Contemporary science teaching faces a disconnection from real-world contexts, leading to demotivation. Interdisciplinary approaches such as STEAM (Science, Technology, Engineering, Arts, and Mathematics) offer an alternative to promote contextualized learning. However, its implementation encounters challenges related to teacher preparation and disposition. Purpose. This paper aims to characterize scientific literature concerning trainee teachers’ attitudes and perceptions towards STEAM education. Analysis. The PRISMA model was applied to articles published between 2016 and 2021 on the Web of Science (WOS) and Scopus. From 128 initial articles, 16 met the selection criteria: language (Spanish or English), focus on attitudes or perceptions towards STEAM, and empirical nature. Results. Quantitative studies predominate, highlighting the need for qualitative research. In-depth training is correlated with positive attitudes towards STEAM, whereas superficial training generates distrust. Conceptual ambiguity and contextual factors, including institutional support and infrastructure, constitute significant barriers. The emotional dimension has a decisive influence on the adoption of the approach. Conclusions. Initial teacher education requires substantial renewal that integrates STEAM as an articulating axis. A clearer understanding of the approach in teacher training, university curriculum updates, innovative training programs, and the development of multidimensional skills is needed. Effective implementation requires a progressive paradigm shift.